Kombinasi Senam Mata dan Pemberian Kencur Dalam Menurunkan Tingkat Nyeri Mata Lelah Pada Penjahit - Adi Sucipto; Fajarina Lathu Asmarani; Nurrohmah Nurrohmah (Poltekkes Kemenkes Surakarta, 2020)
Background: Eye fatigue is often referred to as eye strain or asthenopia. Eye fatigue can be caused by work that requires high focus such as sewing. One of the symptoms of eye fatigue is eye pain. The World Health Organization (WHO) records that the incidence of asthenopia (tired eyes) in the world is an average of 75% per year. The purpose of this study is to determine the effect of a combination therapy between eye exercise and giving kencur (aromatic ginger/Kaempferia galanga) on the pain level of eye fatigue. Methods: This is a quasi-experimental research design with pretest and posttest nonequivalent control group. The research samples were selected using a Non-Probability Sampling technique with a consecutive sampling method. The number of samples selected was 36, they were divided into the experiment group and the control group. Therapy is given once. Bivariate analysis was performed using Wilcoxon test, paired t-test and independent t-test. The research instrument used was the NRS pain scale. Results: The experiment group’s pre-posttest pain scales were 5.06 and 2.78. The control group’s pre-posttest pain scales were 4.50 and 4.00. The bivariate test results of the pre-posttest pain scale of the experiment group and the control group showed p values = 0.000 and 0.001. The results of the bivariate test on the posttest between the experimental group and the control group showed p value = 0.028. Conclusion: Combination of eye exercise and giving kencur has been scientifically proven to reduce eye fatigue better than just eye exercise.